Evidence Based Educational Policy and Practice: The Case of Applying the Educational Effectiveness Knowledge Base - Jaap Scheerens (LED Edizioni Universitarie, 2014)
Evidence based educational policy and practice means, first of all, that new programs use relevant scientific knowledge for design purposes, or for critical review of initial program ideas (ex ante evaluation). Secondly, before programs are implemented on a large scale it is considered desirable to conduct smaller scale try-out and pilots, preferably designed as randomized experiments. Third and finally, rigorous ex post or summative evaluation of the implemented program is to be conducted. In this article the first condition is further analysed. It depends on the availability of broadly confirmed relatively stable research outcomes that make sense in a theoretical and practical way. The illustration that is used in this article is the educational effectiveness knowledge base and its application for decision making on school improvement and educational reform. The state of the art on educational effectiveness research provides some guidelines for successful general reform strategies, but also underlines the limits of malleability in education, in the sense that effect sizes of even the most successful strategies tend to be small.